Perception of the Influence of Practicum Activities on the Learning Outcomes of Biology Education Students at Ahmad Dahlan University - Nulziyati, Nova; Ferdiansyah, Jessica; Mafimudah, Riffatul; Nasrulloh, Hanif; Aprillia, Nani (JURNAL BIOEDUKATIKA, 2023)
This study aims to analyze students' perceptions of practicum activities in relation to their learning outcomes. The method applied is descriptive qualitative analysis, with data collection techniques using questionnaires given to students undergoing practicum at Ahmad Dahlan University. The data obtained was analyzed by thematic analysis methods to find the main themes related to students' experiences and views. The results of this study show that students generally believe that practicum activities have a positive impact on their understanding of theoretical concepts and practical skills they get in class. However, some students also said that there were difficulties related to limited time and inadequate facilities. In addition, support from practicum assistants and direct interaction with practicum tools or instruments are key factors in the success of PR activities.